Comparison of skull dimensions and their respective dentition in relation to its biting forces in Rottweiler, Dobermann, German Shepherd and local dogs in Malaysia - Bay, Jessie Ji Xi (2015)
Since the beginning of domestication, the craniofacial architectures of dogs (Canis lupus familiaris) have changed and modified of a result of human intervention in natural selection. Fatal attacks in humans by dogs have highlight the importance of studying comparative anatomy in forensic science to identify the specific dog breed involved in such an attack. Several studies described the biting forces for specific breeds, but thus far, no such investigation has been conducted in local dogs of Malaysia. Thus, the purpose of this study is to determine the skull dimensions and dentition to estimate and compare the biting forces in Rottweiler, Dobermann, German Shepherd and local dogs in Malaysia. Twenty skulls were obtained from male dogs (five from each different breed) that were disposed at the Post-Mortem Laboratory at the Faculty of Veterinary Medicine, Universiti Putra Malaysia. Skull dimensions were measured using a pair of Vernier caliper on defleshed-dried skulls. Bite forces were estimated using the lever model adapted from Kiltie, 1984. Increasing zygomatic width has a stronger correlation (p<0.01) with biting forces compared to skull length. Rottweiler has the strongest biting forces, compared to Dobermann and German Shepherd. The local dogs have the smallest zygomatic widths, thus the canine and molar biting forces are the weakest. Local dogs are relatively smaller (p<0.05) compared to the other three breeds in terms of skull dimensions and dentition; therefore resulting in the lowest biting forces. The present study revealed that each breed has a distinct skull dimension, dentition and biting forces comparable to other published reports. Due to the high variation observed among local dog in terms of body and skull sizes and overall appearances; future studies should include higher number of local dogs to establish a database of skull dimensions and bite forces which can be valuable information for Malaysian local forensics and crime investigators.